Kalam Khobari in the Book Of Qiṣṣat Al-Miʿrāj By Najmudin Al-Ghaity - Muhammad Kafana Al Kafi; Dayudin Dayudin; Maman Abdul Djaliel (Hasanuddin University, 2025)
This research examines the use of kalam khobari (declarative sentences) in Qiṣṣat al-Miʿrāj, a book that documents the spiritual journey of Prophet Muhammad SAW. The objectives of this study are (1) to identify and classify the types of kalam khobari, including ibtidā’ī, ṭalabī, and inkārī, and (2) to analyze their communicative purposes and functions in conveying spiritual messages. The research employs observation and note-taking as data collection techniques, while using the distributional method to analyze grammatical structures and meanings. The data is presented descriptively and interpretatively. The findings reveal a total of 69 kalam khobari expressions: 5 khabar ibtidā’ī, 53 khabar ṭalabī, and 11 khabar inkārī. The main communicative purposes are categorized into faidah al-khabar (58 instances) and lazīmul faidah (11 instances). Additionally, several secondary functions were identified, including izhār al-fakhr (displaying glory) in 7 sentences, tadzkīr bimā bayna al-marātib (reminding of status differences) in 5, tawbīkh (reproach) in 6, waʿẓ wa irshād (advice and guidance) in 14, izhār al-taḥassur (expressing regret) in 1, and taḥdhīr (warning) in 5 sentences. These results affirm that kalam khobari in Qiṣṣat al-Miʿrāj serves not only an informative function but also contributes significantly to emphasis, correction, motivation, and spiritual guidance within religious communication.